Pengaruh Pelayanan Terhadap Kepuasan Pelanggan PT. PLN (Persero) Rayon Sangatta - Elfreda Aplonia Lau, Siti Nurhasiba LCA Robin Jonathan (EKONOMIA, 2017)
This research is research conducted at PT. PLN (Persero) Rayon Sangatta found some complaints on smart lithrik customers who obtained from some citizens who use prepaid electricity complained of some deficiencies such as power errors, unreadable vouchers and kWh Meter buttons that did not work. The results showed that service quality consisting of Realibility (X1), responsiveness (X2), assurance (X3), emphaty (X4), and tangible (X5) together had a positive influence. Where Regression Equation Y = 0.155 X1 + 0.688 X2 + 0.008 X3 + 0.135 X4 + 0.133 X5. In addition, with F test it is seen that the quality of service has a significant effect on customer satisfaction with the F value count of 40,579 with a significance value of 0.000. Based on the partial t test, all the variables have a significant influence on customer satisfaction with a significant value of 0,000 with t hitunng value for Tangible (X1) of 10.632, Reliability (X2) of 11.066, Resposiveness (X3) of 11.106, Assurance (X4) of 10.138 and Empaty (X5) of 9,573. Based on the results of hypothesis testing obtained conclusion that there is a positive influence between service to satisfaction perceived by customers using Smart Power PT. PLN (Persero) Rayon Sangatta.